A method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal
By applying an applied magnetic field in the electrochemical system and measuring the corrosion depth of the ferromagnetic metal surface, combined with Comsol simulation, the problem of difficult to measure the magnetic induction intensity distribution of the ferromagnetic metal surface is solved, and efficient and accurate measurement of magnetic induction intensity is achieved.
Patent Information
- Application Number
- CN202110916436.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-11
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-08-11
AI Technical Summary
The prior art is difficult to effectively measure the distribution of magnetic induction intensity on the surface of ferromagnetic metals, resulting in uneven electrode surface morphology and corrosion depth after polarization.
By applying an external magnetic field to the electrochemical system, the surface corrosion depth after ferromagnetic metal polarization is measured, and the distribution of magnetic induction intensity on the surface of ferromagnetic electrodes is simulated by Comsol Multiphysics to judge the distribution of magnetic induction intensity on the metal surface.
It realizes the distribution of magnetic induction intensity of ferromagnetic metal surfaces to be concise and efficiently determined, improves the measurement accuracy and repeatability of magnetic induction intensity, and is low in cost, which is suitable for promotion and use.
Smart Images

Figure CN114675220B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic induction intensity measurement, and in particular relates to a method for measuring the magnetic induction intensity distribution on the surface of a ferromagnetic metal. Background Art
[0002] Magnetic induction intensity is a physical quantity that describes the strength of a magnetic field and is an important physical parameter in electromagnetism. The surface of a ferromagnetic metal placed in a magnetic field will generate an induced magnetic field. The distribution of the induced magnetic field intensity is affected by many factors, such as the metal's magnetic susceptibility, geometry, and size. There are limitations to using physical methods to test the magnetic induction intensity of a ferromagnetic metal surface. When a magnetic field is applied during the electrochemical polarization process, the uneven distribution of the magnetic induction intensity on the surface of a ferromagnetic metal electrode will lead to uneven electrode surface morphology after polarization and uneven corrosion depth. Therefore, how to measure the distribution of magnetic induction intensity on a metal surface has become a technical problem that needs to be solved urgently. Summary of the invention
[0003] In order to solve the problems of the prior art, the purpose of the present invention is to overcome the shortcomings of the existing technology and provide a method for measuring the distribution of magnetic induction intensity on the surface of ferromagnetic metal. By measuring the surface corrosion depth of the ferromagnetic metal after polarization under an external magnetic field, the distribution of magnetic induction intensity on the metal surface can be judged.
[0004] In order to achieve the above invention purpose, the present invention adopts the following technical solution:
[0005] A method for measuring the magnetic induction intensity distribution on the surface of a ferromagnetic metal, the method comprising the following steps:
[0006] Step 1: Electrode system preparation:
[0007] A ferromagnetic working electrode, a reference electrode and an auxiliary electrode are used to form a three-electrode system, which is connected to an electrochemical workstation to form an electrode system;
[0008] Step 2: Potentiodynamic scanning:
[0009] The working electrode of the electrode system is immersed in a corrosive solution until the self-corrosion potential reaches a stable state; the electrochemical system is subjected to a dynamic potential scan under the condition of no magnetic field or an applied magnetic field, and the applied magnetic field strength is 0.05-1.2T, and the dynamic potential scan starts from the open circuit potential and ends at the over-passivation zone potential;
[0010] Step 3: Perform constant potential polarization under applied magnetic field:
[0011] According to the dynamic potential scanning curve of the ferromagnetic working electrode with and without a magnetic field, the potential interval where the magnetic field has an influence is determined, and a magnetic field is applied at a certain potential in the potential interval for constant potential polarization, and the applied magnetic field strength is 0.05-1.2T;
[0012] Step 4: Determine the distribution of magnetic induction intensity on the working electrode surface:
[0013] Observe the corrosion morphology of the surface of the ferromagnetic working electrode after constant potential polarization, quantify the distribution of corrosion depth on the electrode surface, and determine the surface magnetic induction intensity distribution based on the corrosion depth distribution of the ferromagnetic working electrode after constant potential polarization;
[0014] Step 5: Use Comsol Multiphysics to simulate the distribution of magnetic induction intensity on the surface of ferromagnetic electrodes:
[0015] The magnetic field under the AC / DC module in Comsol software was selected as the physical field interface. A simulation model consistent with the experiment was established, the required material properties were added, and the input current generated a magnetic field strength corresponding to the experiment. The distribution of magnetic induction intensity on the surface of the ferromagnetic electrode was calculated using the grid division steps. According to the simulated distribution of magnetic induction intensity, the corrosion depth after constant potential polarization was verified, and the distribution of magnetic induction intensity on the surface of the ferromagnetic working electrode was determined.
[0016] Preferably, the temperature of all processes in the method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal is the same temperature. Further preferably, the temperature of all processes is room temperature.
[0017] Preferably, all processes of the method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal are repeated no less than 3 times.
[0018] As a preferred technical solution, in steps 2 to 5, the strength of the applied magnetic field is 0.05-0.4T.
[0019] As another preferred technical solution, in steps 2 to 5, the strength of the applied magnetic field is 0.4-0.8T.
[0020] As another preferred technical solution, in steps 2 to 5, the strength of the external magnetic field is 0.8-1.2T.
[0021] Preferably, in step 1, the working electrode is an industrial pure Fe electrode with a diameter of not less than 5 mm, the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum sheet electrode.
[0022] Preferably, in step 2, the working electrode of the electrode system is immersed in a corrosive solution until the self-corrosion potential reaches a stable state; the electrochemical system is subjected to a dynamic potential scan under the condition of no magnetic field or an applied magnetic field, the applied magnetic field strength is 0.05-1.2T, and the dynamic potential scan starts from the open circuit potential to the over-passivation zone potential; the immersion time is at least 30min, and the solution is H with a concentration of not less than 1mol / L 2 SO 4, the scanning potential is 0V (vs.OCP) to 2V (vs.SCE); the external magnetic field is horizontal, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field intensity is 0.2-0.4T;
[0023] Preferably, in the step three, the potential interval affected by the magnetic field is determined according to the dynamic potential scanning curve of the ferromagnetic working electrode with and without a magnetic field, and a magnetic field is applied at a certain potential in the potential interval for constant potential polarization; the polarization potential is at least 0.1V, and the polarization time is at least 600s; the external magnetic field is horizontal, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field strength is 0.2-0.4T;
[0024] Preferably, in the step 4, the surface morphology of the ferromagnetic metal working electrode after constant potential polarization is observed, and the corrosion depth of the electrode surface is quantified by the following method:
[0025] Under the condition of magnetic field strength of 0.2-0.4T, the Fe 2 SO 4 The electrode surface morphology and corrosion depth after constant potential polarization in the solution; the corrosion in the central area of the ferromagnetic metal surface is shallow, and the magnetic induction intensity is small; the left and right areas of the ferromagnetic metal surface are nearly left-right symmetrical with the central area as the axis, and the corrosion in the left and right areas of the ferromagnetic metal surface is deeper than that in the central area of the ferromagnetic metal surface, and the magnetic induction intensity is larger;
[0026] Preferably, in step five, the magnetic field under the AC / DC module in the Comsol software is selected as the physical field interface, and a simulation model consistent with the experiment is established, the required material properties are added, and the input current generates a magnetic field strength corresponding to the experiment. The distribution of the magnetic induction intensity on the surface of the ferromagnetic electrode is calculated using a grid division step. According to the simulated distribution of the magnetic induction intensity, the corrosion depth after constant potential polarization is verified, and the distribution of the magnetic induction intensity on the surface of the ferromagnetic working electrode is determined; the relative magnetic permeability of the ferromagnetic working electrode is defined as 4000, and a current of 2.63-5.26A is input to generate a magnetic field intensity of 0.2-0.4T. The magnetic flux lines are parallel to the ferromagnetic metal surface, and the surface of the ferromagnetic working electrode is divided using a tetrahedral grid, and the simulation result is along the direction of the magnetic flux lines.
[0027] Compared with the prior art, the present invention has the following obvious outstanding substantive features and significant advantages:
[0028] 1. The present invention can determine the distribution of magnetic induction intensity on the surface of ferromagnetic metal simply and efficiently by observing the corrosion depth of the electrode surface after constant potential polarization of the ferromagnetic metal, and effectively improve the measurement of magnetic induction intensity;
[0029] 2. The measurement repeatability of the present invention is good and the measurement process is easy to control;
[0030] 3. The method of the present invention is simple, easy to implement, low in cost, and suitable for popularization and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 In Example 1 of the present invention, Fe in 1 mol / LH 2 SO 4 Surface morphology and corrosion depth after constant potential polarization in solution. The inset (a) shows the surface morphology of the ferromagnetic electrode after constant potential polarization; the inset (b) shows the corrosion depth at the electrode diameter.
[0032] Figure 2 This is the distribution of magnetic induction intensity on the surface of the Fe electrode under Comsol simulation of an external 0.4T magnetic field in Example 1 of the present invention.
[0033] Figure 3 In Example 2 of the present invention, Fe in 1 mol / LH 2 SO 4 Surface morphology and corrosion depth after constant potential polarization in solution. The inset (a) shows the surface morphology of the ferromagnetic electrode after constant potential polarization; the inset (b) shows the corrosion depth at the electrode diameter.
[0034] Figure 4 This is the distribution of magnetic induction intensity on the Fe electrode surface under Comsol simulation of an external 0.2T magnetic field in Example 2 of the present invention.
[0035] Figure 5 In Example 3 of the present invention, Fe in 1 mol / LH 2 SO 4 Surface morphology and corrosion depth after constant potential polarization in solution. The inset (a) shows the surface morphology of the ferromagnetic electrode after constant potential polarization; the inset (b) shows the corrosion depth at the electrode diameter.
[0036] Figure 6 This is the distribution of magnetic induction intensity on the Fe electrode surface under Comsol simulation of Example 3 of the present invention under the condition of an external 0.05T magnetic field.
[0037] Figure 7 In Example 4 of the present invention, Fe in 1 mol / LH 2 SO 4 Surface morphology and corrosion depth after constant potential polarization in solution. The inset (a) shows the surface morphology of the ferromagnetic electrode after constant potential polarization; the inset (b) shows the corrosion depth at the electrode diameter.
[0038] Figure 8 This is the distribution of magnetic induction intensity on the Fe electrode surface under Comsol simulation of Example 4 of the present invention under an external 0.8T magnetic field condition.
[0039] Fig. 9 In Example 5 of the present invention, Fe in 1 mol / L H 2 SO 4 Surface morphology and corrosion depth after constant potential polarization in solution. The inset (a) shows the surface morphology of the ferromagnetic electrode after constant potential polarization; the inset (b) shows the corrosion depth at the electrode diameter.
[0040] Fig.10 This is the distribution of magnetic induction intensity on the Fe electrode surface under Comsol simulation of Example 5 of the present invention under an external 1.2T magnetic field condition. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below through specific implementation methods in combination with the accompanying drawings, but is not limited thereto. Any technical solution obtained by modifying the technical solution of the present invention or adopting equivalent replacement or equivalent change shall fall within the protection scope of the present invention.
[0042] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:
[0043] Embodiment 1:
[0044] In this embodiment, a method for measuring the magnetic induction intensity distribution on the surface of a ferromagnetic metal is provided. At room temperature, the method comprises the following steps:
[0045] Step 1: Electrode system preparation
[0046] The ferromagnetic metal working electrode, reference electrode and auxiliary electrode constitute a three-electrode system and are connected to the electrochemical workstation; the working electrode is industrial pure Fe with a diameter of 5 mm, the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum sheet;
[0047] Step 2: Potentiodynamic Scanning
[0048] The working electrode was immersed in a corrosive solution. When the self-corrosion potential reached a stable state, the electrochemical system was subjected to a dynamic potential scan under the conditions of no magnetic field or applied magnetic field. The dynamic potential scan started from the open circuit potential and ended at the passivation zone potential. The immersion time was 30 minutes, and the solution was 1 mol / L H 2 SO 4 , the scanning potential is from 0 V (vs. OCP) to 2 V (vs. SCE); the external magnetic field is in the horizontal direction, the magnetic field direction is parallel to the working electrode surface, and the magnetic field intensity is 0.4 T;
[0049] Step 3: Constant Potential Polarization
[0050] According to the dynamic potential scanning curve of the ferromagnetic metal working electrode with and without a magnetic field, the potential interval affected by the magnetic field is determined, and a magnetic field is applied at a certain potential in this potential interval for constant potential polarization. The polarization potential is 0.1V, and the polarization time is 600s; the external magnetic field is horizontal, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field intensity is 0.4T;
[0051] Step 4: Determine the magnetic induction intensity distribution on the working electrode surface
[0052] Observe the surface morphology of the ferromagnetic metal working electrode after constant potential polarization, and quantify the corrosion depth of the electrode surface: the greater the corrosion depth of the ferromagnetic metal surface, the greater the magnetic induction intensity of the ferromagnetic metal surface; under 0.4T conditions, Fe in 1mol / LH 2 SO 4 The electrode surface morphology and corrosion depth after constant potential polarization in solution are as follows: Figure 1 As shown, the central area of the ferromagnetic metal surface is less corroded, and the magnetic induction intensity is smaller; the left and right areas are nearly symmetrical with the central area as the axis, and the left and right areas are relatively deeply corroded, and the magnetic induction intensity is larger;
[0053] Step 5: Comsol Multiphysics simulates the distribution of magnetic induction intensity on the surface of ferromagnetic electrodes
[0054] The magnetic field under the AC / DC module in Comsol software was selected as the physical field interface. A simulation model consistent with the experiment was established, the required material properties were added, and the input current generated the magnetic field strength corresponding to the experiment. The meshing step calculated the distribution of the magnetic induction intensity on the surface of the ferromagnetic electrode. The simulated distribution of the magnetic induction intensity was verified by the corrosion depth after constant potential polarization to determine the distribution of the magnetic induction intensity on the surface of the ferromagnetic working electrode. The relative magnetic permeability of pure iron was defined as 4000, and the input current of 5.26A generated a magnetic field intensity of 0.4T. The magnetic flux lines were parallel to the surface of the ferromagnetic metal. The pure iron was divided into tetrahedral meshes. The simulation results showed that along the direction of the magnetic flux lines, the magnetic induction intensity on both sides of the edge of the ferromagnetic metal Fe was large and gradually decreased toward the center of the metal, such as Figure 2 This embodiment can determine the distribution of magnetic induction intensity on the surface of ferromagnetic metal simply and efficiently by observing the corrosion depth of the electrode surface after constant potential polarization of the ferromagnetic metal, thereby effectively improving the measurement of magnetic induction intensity.
[0055] Embodiment 2
[0056] This embodiment is basically the same as the first embodiment, except that:
[0057] In this embodiment, a method for measuring the magnetic induction intensity distribution on the surface of a ferromagnetic metal is provided. At room temperature, the method comprises the following steps:
[0058] Step 1: Electrode system preparation
[0059] The working electrode, reference electrode and auxiliary electrode constitute a three-electrode system and are connected to the electrochemical workstation; the working electrode is industrial pure Fe with a diameter of 5 mm, the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum sheet;
[0060] Step 2: Potentiodynamic Scanning
[0061] The working electrode was immersed in a corrosive solution. When the self-corrosion potential reached a stable state, the electrochemical system was subjected to a dynamic potential scan under the conditions of no magnetic field or applied magnetic field. The dynamic potential scan started from the open circuit potential and ended at the passivation zone potential. The immersion time was 30 minutes, and the solution was 1 mol / L H 2 SO 4 , the scanning potential is 0V (vs. OCP) to 2V (vs. SCE). The external magnetic field is horizontal, the magnetic field direction is parallel to the working electrode surface, and the magnetic field intensity is 0.2T;
[0062] Step 3: Constant Potential Polarization
[0063] According to the dynamic potential scanning curve of the ferromagnetic metal working electrode with and without a magnetic field, the potential interval where the magnetic field has an influence is determined, and a magnetic field is applied at a certain potential in the potential interval for constant potential polarization; the polarization potential is 0.1V, and the polarization time is 600s; the external magnetic field is horizontal, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field intensity is 0.2T;
[0064] Step 4: Determine the magnetic induction intensity distribution on the electrode surface
[0065] Observe the surface morphology of the ferromagnetic metal working electrode after constant potential polarization, and quantify the corrosion depth of the electrode surface. According to the surface corrosion morphology and corrosion depth distribution of the ferromagnetic metal working electrode after constant potential polarization, determine the surface magnetic induction intensity distribution: the greater the corrosion depth of the ferromagnetic metal surface, the greater the magnetic induction intensity of the ferromagnetic metal surface; under 0.2T conditions, Fe in 1mol / LH 2 SO 4 The electrode surface morphology and corrosion depth after constant potential polarization in solution are as follows: Figure 3 As shown in the figure, the central area of the ferromagnetic metal surface is less corroded and has a smaller magnetic induction intensity; the left and right areas are nearly symmetrical with the central area as the axis, and the left and right areas are relatively deeply corroded and have a larger magnetic induction intensity;
[0066] Step 5: Comsol Multiphysics simulates the distribution of magnetic induction intensity on the surface of ferromagnetic electrodes
[0067] The magnetic field under the AC / DC module in Comsol software was selected as the physical field interface. A simulation model consistent with the experiment was established, the required material properties were added, and the input current generated the magnetic field strength corresponding to the experiment. The meshing step calculated the distribution of the magnetic induction intensity on the surface of the ferromagnetic electrode. The method of judging the distribution of the magnetic induction intensity on the surface of the ferromagnetic working electrode by the corrosion depth after constant potential polarization was verified based on the simulated distribution of the magnetic induction intensity. The relative magnetic permeability of pure iron was defined as 4000, and the input current of 2.63A generated a magnetic field intensity of 0.2T. The magnetic flux lines were parallel to the surface of the ferromagnetic metal. The pure iron was divided into tetrahedral meshes. The simulation results showed that along the direction of the magnetic flux lines, the magnetic induction intensity on both sides of the edge of the ferromagnetic metal Fe was large and gradually decreased toward the center of the metal, such as Figure 4 This embodiment can determine the distribution of magnetic induction intensity on the surface of ferromagnetic metal simply and efficiently by observing the corrosion depth of the electrode surface after constant potential polarization of the ferromagnetic metal, thereby effectively improving the measurement of magnetic induction intensity.
[0068] Embodiment 3
[0069] This embodiment is basically the same as the above embodiment, with the following features:
[0070] In this embodiment, a method for measuring the magnetic induction intensity distribution on the surface of a ferromagnetic metal is provided. At room temperature, the method comprises the following steps:
[0071] Step 1: Electrode system preparation
[0072] The working electrode, reference electrode and auxiliary electrode constitute a three-electrode system and are connected to the electrochemical workstation; the working electrode is industrial pure Fe with a diameter of 5 mm, the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum sheet;
[0073] Step 2: Potentiodynamic Scanning
[0074] The working electrode was immersed in a corrosive solution. When the self-corrosion potential reached a stable state, the electrochemical system was subjected to a dynamic potential scan under the conditions of no magnetic field or applied magnetic field. The dynamic potential scan started from the open circuit potential and ended at the passivation zone potential. The immersion time was 30 min, and the solution was 1 mol / L H 2 SO 4 , the scanning potential is from 0 V (vs. OCP) to 2 V (vs. SCE); the external magnetic field is in the horizontal direction, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field intensity is 0.05 T;
[0075] Step 3: Constant Potential Polarization
[0076] According to the dynamic potential scanning curve of the ferromagnetic metal working electrode with and without a magnetic field, the potential interval affected by the magnetic field is determined, and a magnetic field is applied at a certain potential in this potential interval for constant potential polarization. The polarization potential is 0.1V, and the polarization time is 600s. The external magnetic field is horizontal, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field intensity is 0.05T;
[0077] Step 4: Determine the magnetic induction intensity distribution on the electrode surface
[0078] Observe the surface morphology of the ferromagnetic metal working electrode after constant potential polarization, and quantify the corrosion depth of the electrode surface. According to the surface corrosion morphology and corrosion depth distribution of the ferromagnetic metal working electrode after constant potential polarization, determine the surface magnetic induction intensity distribution: the greater the corrosion depth of the ferromagnetic metal surface, the greater the magnetic induction intensity of the ferromagnetic metal surface; under 0.05T conditions, Fe in 1mol / LH 2 SO 4 The electrode surface morphology and corrosion depth after constant potential polarization in solution are as follows: Figure 5 As shown: the central area of the ferromagnetic metal surface is less corroded, and the magnetic induction intensity is smaller; the left and right areas are nearly symmetrical with the central area as the axis, the left and right areas are relatively deeply corroded, and the magnetic induction intensity is larger;
[0079] Step 5: Comsol Multiphysics simulates the distribution of magnetic induction intensity on the surface of ferromagnetic electrodes
[0080] The magnetic field under the AC / DC module in Comsol software was selected as the physical field interface. A simulation model consistent with the experiment was established, the required material properties were added, and the input current generated the magnetic field strength corresponding to the experiment. The meshing step calculated the distribution of the magnetic induction intensity on the surface of the ferromagnetic electrode. The method of judging the distribution of the magnetic induction intensity on the surface of the ferromagnetic working electrode by the corrosion depth after constant potential polarization was verified based on the simulated distribution of the magnetic induction intensity. The relative magnetic permeability of pure iron was defined as 4000, and the input current of 0.6575A generated a magnetic field intensity of 0.05T. The magnetic flux lines were parallel to the surface of the ferromagnetic metal. The pure iron was divided into tetrahedral meshes. The simulation results showed that along the direction of the magnetic flux lines, the magnetic induction intensity on both sides of the edge of the ferromagnetic metal Fe was large and gradually decreased toward the center of the metal, such as Figure 6 This embodiment can determine the distribution of magnetic induction intensity on the surface of ferromagnetic metal simply and efficiently by observing the corrosion depth of the electrode surface after constant potential polarization of the ferromagnetic metal, thereby effectively improving the measurement of magnetic induction intensity.
[0081] Embodiment 4
[0082] This embodiment is basically the same as the above embodiment, with the following features:
[0083] In this embodiment, a method for measuring the magnetic induction intensity distribution on the surface of a ferromagnetic metal is provided. At room temperature, the method comprises the following steps:
[0084] Step 1: Electrode system preparation
[0085] The working electrode, reference electrode and auxiliary electrode constitute a three-electrode system and are connected to the electrochemical workstation; the working electrode is industrial pure Fe with a diameter of 5 mm, the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum sheet;
[0086] Step 2: Potentiodynamic Scanning
[0087] The working electrode was immersed in a corrosive solution. When the self-corrosion potential reached a stable state, the electrochemical system was subjected to a dynamic potential scan under the conditions of no magnetic field or applied magnetic field. The dynamic potential scan started from the open circuit potential and ended at the passivation zone potential. The immersion time was 30 min, and the solution was 1 mol / L H 2 SO 4 , the scanning potential is from 0 V (vs. OCP) to 2 V (vs. SCE); the external magnetic field is in the horizontal direction, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field intensity is 0.8 T;
[0088] Step 3: Constant Potential Polarization
[0089] According to the dynamic potential scanning curve of the ferromagnetic metal working electrode with and without a magnetic field, the potential interval affected by the magnetic field is determined, and a magnetic field is applied at a certain potential in this potential interval for constant potential polarization. The polarization potential is 0.1V, and the polarization time is 600s. The external magnetic field is horizontal, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field intensity is 0.8T;
[0090] Step 4: Determine the magnetic induction intensity distribution on the electrode surface
[0091] Observe the surface morphology of the ferromagnetic metal working electrode after constant potential polarization, and quantify the corrosion depth of the electrode surface. According to the surface corrosion morphology and corrosion depth distribution of the ferromagnetic metal working electrode after constant potential polarization, determine the surface magnetic induction intensity distribution: the greater the corrosion depth of the ferromagnetic metal surface, the greater the magnetic induction intensity of the ferromagnetic metal surface; under 0.8T conditions, Fe in 1mol / LH 2 SO 4 The electrode surface morphology and corrosion depth after constant potential polarization in solution are as follows: Figure 7 As shown: the central area of the ferromagnetic metal surface is less corroded, and the magnetic induction intensity is smaller; the left and right areas are nearly symmetrical with the central area as the axis, the left and right areas are relatively deeply corroded, and the magnetic induction intensity is larger;
[0092] Step 5: Comsol Multiphysics simulates the distribution of magnetic induction intensity on the surface of ferromagnetic electrodes
[0093] The magnetic field under the AC / DC module in Comsol software was selected as the physical field interface. A simulation model consistent with the experiment was established, the required material properties were added, and the input current generated the magnetic field strength corresponding to the experiment. The meshing step calculated the distribution of the magnetic induction intensity on the surface of the ferromagnetic electrode. The method of judging the distribution of the magnetic induction intensity on the surface of the ferromagnetic working electrode by the corrosion depth after constant potential polarization was verified based on the simulated distribution of the magnetic induction intensity. The relative magnetic permeability of pure iron was defined as 4000, and the input current of 10.52A generated a magnetic field intensity of 0.8T. The magnetic flux lines were parallel to the surface of the ferromagnetic metal. The pure iron was divided into tetrahedral meshes. The simulation results showed that along the direction of the magnetic flux lines, the magnetic induction intensity on both sides of the edge of the ferromagnetic metal Fe was large and gradually decreased toward the center of the metal, such as Figure 8 This embodiment can determine the distribution of magnetic induction intensity on the surface of ferromagnetic metal simply and efficiently by observing the corrosion depth of the electrode surface after constant potential polarization of the ferromagnetic metal, thereby effectively improving the measurement of magnetic induction intensity.
[0094] Embodiment 5
[0095] This embodiment is basically the same as the above embodiment, with the following features:
[0096] In this embodiment, a method for measuring the magnetic induction intensity distribution on the surface of a ferromagnetic metal is provided. At room temperature, the method comprises the following steps:
[0097] Step 1: Electrode system preparation
[0098] The working electrode, reference electrode and auxiliary electrode constitute a three-electrode system and are connected to the electrochemical workstation; the working electrode is industrial pure Fe with a diameter of 5 mm, the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum sheet;
[0099] Step 2: Potentiodynamic Scanning
[0100] The working electrode was immersed in a corrosive solution. When the self-corrosion potential reached a stable state, the electrochemical system was subjected to a dynamic potential scan under the conditions of no magnetic field or applied magnetic field. The dynamic potential scan started from the open circuit potential and ended at the passivation zone potential. The immersion time was 30 min, and the solution was 1 mol / L H 2 SO 4 , the scanning potential is from 0 V (vs. OCP) to 2 V (vs. SCE); the external magnetic field is in the horizontal direction, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field intensity is 1.2 T;
[0101] Step 3: Constant Potential Polarization
[0102] According to the dynamic potential scanning curve of the ferromagnetic metal working electrode with and without a magnetic field, the potential interval affected by the magnetic field is determined, and a magnetic field is applied at a certain potential in this potential interval for constant potential polarization. The polarization potential is 0.1V, and the polarization time is 600s. The external magnetic field is horizontal, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field intensity is 1.2T;
[0103] Step 4: Determine the magnetic induction intensity distribution on the electrode surface
[0104] Observe the surface morphology of the ferromagnetic metal working electrode after constant potential polarization, and quantify the corrosion depth of the electrode surface. According to the surface corrosion morphology and corrosion depth distribution of the ferromagnetic metal working electrode after constant potential polarization, determine the surface magnetic induction intensity distribution: the greater the corrosion depth of the ferromagnetic metal surface, the greater the magnetic induction intensity of the ferromagnetic metal surface; under 1.2T conditions, Fe in 1mol / LH 2 SO 4 The electrode surface morphology and corrosion depth after constant potential polarization in solution are as follows: Fig. 9 As shown: the central area of the ferromagnetic metal surface is less corroded, and the magnetic induction intensity is smaller; the left and right areas are nearly symmetrical with the central area as the axis, the left and right areas are relatively deeply corroded, and the magnetic induction intensity is larger;
[0105] Step 5: Comsol Multiphysics simulates the distribution of magnetic induction intensity on the surface of ferromagnetic electrodes
[0106] The magnetic field under the AC / DC module in Comsol software was selected as the physical field interface. A simulation model consistent with the experiment was established, the required material properties were added, and the input current generated the magnetic field strength corresponding to the experiment. The meshing step calculated the distribution of the magnetic induction intensity on the surface of the ferromagnetic electrode. The method of judging the distribution of the magnetic induction intensity on the surface of the ferromagnetic working electrode by the corrosion depth after constant potential polarization was verified based on the simulated distribution of the magnetic induction intensity. The relative magnetic permeability of pure iron was defined as 4000, and the input current of 15.78A generated a magnetic field intensity of 1.2T. The magnetic flux lines were parallel to the surface of the ferromagnetic metal. The pure iron was divided into tetrahedral meshes. The simulation results showed that along the direction of the magnetic flux lines, the magnetic induction intensity on both sides of the edge of the ferromagnetic metal Fe was large and gradually decreased toward the center of the metal, such as Fig.10 This embodiment can determine the distribution of magnetic induction intensity on the surface of ferromagnetic metal simply and efficiently by observing the corrosion depth of the electrode surface after constant potential polarization of the ferromagnetic metal, thereby effectively improving the measurement of magnetic induction intensity.
[0107] In summary, the above embodiment is a method for measuring the distribution of magnetic induction intensity on the surface of ferromagnetic metal, which belongs to the field of magnetic induction intensity measurement technology. The method includes: electrode system preparation, electrochemical system is subjected to potentiodynamic scanning under the condition of no magnetic field or applied magnetic field; according to the potentiodynamic curve, the potential that has an impact on the magnetic field is selected to perform constant potential polarization under the condition of applying a magnetic field, and the magnetic field intensity is 0.05-1.2T; observe the surface morphology of the working electrode after constant potential polarization, and use Comsol Multiphysics to simulate the distribution of magnetic induction intensity on the surface of the ferromagnetic electrode, and verify the distribution of magnetic induction intensity by corrosion depth according to Comsol software simulation. The three-dimensional morphology of the ferromagnetic metal surface in the above embodiment is ridge-shaped, and the fluctuation of the magnetic induction intensity distribution on the ferromagnetic metal surface is correlated with the surface depth of the ferromagnetic metal surface. The present invention introduces a magnetic field in the electrochemical system, and measures the distribution of magnetic induction intensity on the ferromagnetic metal surface by observing the corrosion depth of the electrode surface after polarization.
[0108] The above describes the embodiments of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made according to the purpose of the invention. Any changes, modifications, substitutions, combinations or simplifications made according to the spirit and principle of the technical solution of the present invention should be equivalent replacement methods. As long as they meet the purpose of the invention and do not deviate from the technical principles and inventive concepts of the present invention, they belong to the protection scope of the present invention.
Claims
1. A method for measuring the magnetic induction intensity distribution on the surface of a ferromagnetic metal, characterized in that: The method comprises the following steps: Step 1: Electrode system preparation: A ferromagnetic working electrode, a reference electrode and an auxiliary electrode are used to form a three-electrode system, which is connected to an electrochemical workstation to form an electrode system; Step 2: Potentiodynamic scanning: The working electrode of the electrode system is immersed in a corrosive solution until the self-corrosion potential reaches a stable state; the electrochemical system is subjected to a dynamic potential scan under the condition of no magnetic field or an applied magnetic field, and the applied magnetic field strength is 0.05-1.2T, and the dynamic potential scan starts from the open circuit potential and ends at the over-passivation zone potential; Step 3: Perform constant potential polarization under applied magnetic field conditions: According to the dynamic potential scanning curve of the ferromagnetic working electrode with and without a magnetic field, the potential interval where the magnetic field has an influence is determined, and a magnetic field is applied at a certain potential in the potential interval for constant potential polarization, and the applied magnetic field strength is 0.05-1.2T; Step 4: Determine the distribution of magnetic induction intensity on the working electrode surface: Observe the corrosion morphology of the surface of the ferromagnetic working electrode after constant potential polarization, quantify the distribution of corrosion depth on the electrode surface, and determine the surface magnetic induction intensity distribution based on the corrosion depth distribution of the ferromagnetic working electrode after constant potential polarization; Step 5: Use Comsol Multiphysics to simulate the distribution of magnetic induction intensity on the surface of ferromagnetic electrodes: The magnetic field under the AC / DC module in Comsol software was selected as the physical field interface. A simulation model consistent with the experiment was established, the required material properties were added, and the input current generated a magnetic field strength corresponding to the experiment. The distribution of magnetic induction intensity on the surface of the ferromagnetic electrode was calculated using the grid division steps. According to the simulated distribution of magnetic induction intensity, the corrosion depth after constant potential polarization was verified, and the distribution of magnetic induction intensity on the surface of the ferromagnetic working electrode was determined.
2. The method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal according to claim 1, characterized in that: The temperature of all processes is the same.
3. The method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal according to claim 2, characterized in that: The temperature of all processes is room temperature.
4. The method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal according to claim 1, characterized in that: All processes were repeated no less than 3 times.
5. The method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal according to claim 1, characterized in that: In the steps 2 to 5, the strength of the applied magnetic field is 0.05-0.4T.
6. The method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal according to claim 1, characterized in that: In the steps 2 to 5, the strength of the applied magnetic field is 0.4-0.8T.
7. The method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal according to claim 1, characterized in that: In the steps 2 to 5, the strength of the applied magnetic field is 0.8-1.2T.
8. The method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal according to claim 1, characterized in that: In the step 1, the working electrode is an industrial pure Fe electrode with a diameter of not less than 5 mm, the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum sheet electrode.
9. The method for measuring the magnetic induction intensity distribution on the surface of ferromagnetic metal according to claim 1, characterized in that: In the step 2, the working electrode of the electrode system is immersed in a corrosive solution until the self-corrosion potential reaches a stable state; the electrochemical system is subjected to a dynamic potential scan under the condition of no magnetic field or applied magnetic field, the external magnetic field strength is 0.02-1.2T, and the dynamic potential scan starts from the open circuit potential to the over-passivation zone potential; the immersion time is at least 30min, the solution is H2SO4 with a concentration of not less than 1mol / L, and the scanning potential is 0V (vs.OCP) to 2V (vs.SCE); the external magnetic field is horizontal, the magnetic field direction is parallel to the surface of the working electrode, and the magnetic field strength is 0.2-0.4T; Alternatively, in the step three, the potential interval in which the magnetic field has an influence is determined according to the dynamic potential scanning curve of the ferromagnetic working electrode with and without a magnetic field, and a magnetic field is applied at a certain potential in the potential interval for constant potential polarization; the polarization potential is at least 0.1V, and the polarization time is at least 600s; the external magnetic field is horizontal, the direction of the magnetic field is parallel to the surface of the working electrode, and the magnetic field strength is 0.2-0.4T; Alternatively, in step 4, the surface morphology of the ferromagnetic metal working electrode after constant potential polarization is observed to quantify the corrosion depth of the electrode surface by the following method: Under the condition of magnetic field strength of 0.2-0.4T, the electrode surface morphology and corrosion depth of Fe after constant potential polarization in 1mol / L H2SO4 solution were observed; the central area of the ferromagnetic metal surface was shallowly corroded, and the magnetic induction intensity was small; the left and right areas of the ferromagnetic metal surface were nearly left-right symmetrical with the central area as the axis, and the corrosion of the left and right areas of the ferromagnetic metal surface was deeper than that of the central area of the ferromagnetic metal surface, and the magnetic induction intensity was large; Alternatively, in step five, the magnetic field under the AC / DC module in the Comsol software is selected as the physical field interface, and a simulation model consistent with the experiment is established, the required material properties are added, and the input current generates a magnetic field strength corresponding to the experiment. The distribution of the magnetic induction intensity on the surface of the ferromagnetic electrode is calculated using a meshing step, and the corrosion depth after constant potential polarization is verified based on the simulated distribution of the magnetic induction intensity, and the distribution of the magnetic induction intensity on the surface of the ferromagnetic working electrode is determined; the relative magnetic permeability of the ferromagnetic working electrode is defined as 4000, and a current of 2.63-5.26A is input to generate a magnetic field intensity of 0.2-0.4T, the magnetic flux lines are parallel to the ferromagnetic metal surface, and the surface of the ferromagnetic working electrode is divided using a tetrahedral mesh, and the simulation result is along the direction of the magnetic flux lines.
Citation Information
Patent Citations
Micro-electro-mechanical system magnetic field sensor and magnetic field measurement method
CN101059557A
Placement type probe and visual quantitative evaluation method for damage detection of metal component
CN108195931A